Contamination level and risk assessment of heavy metal deposited in street dusts in Khamees-Mushait city, Saudi Arabia. Issue 2 (7th February 2020) - Idris, Abubakr M.; Alqahtani, Fatima M.S.; Said, Tarek O.; Fawy, Khaled F.
Abstract: The levels of some potentially toxic metals (Cr, Mn, Fe, Co, Cu, Zn, Cd, and Pb) were quantified in 60 street dust samples from Khamees-Mushait city, Saudi Arabia. Samples were taken from three locations at each functional area (total 18 including traffic, industrial, residential, and workshops) and at each control area (total two including a park and a new domestic planner). Heavy metals concentrations were quantified in less than 106 µm particle-size using inductively-coupled plasma-optical emission spectrometer after microwave wet digestion. The total concentrations (µg/g) were in the ranges of Cr 128.48–277.53, Mn 589.43–1091.45, Fe 43478.26–99151.63, Co 23.04–55.22, Cu 10.46–176.13, Cd 0.30–1.99, and Pb 9.36–340.56. The accuracy of results was examined using standard quality control samples, spiking, and a certified reference material. The overall recovery was in the range of 86.2–113.3%. The enrichment factors and the geoaccumulation indices, besides principal component analysis, reveal various levels of enrichment by Fe, Cu, Zn, and Pb from functional areas of congested traffic, commercial activities, and metallic workshops activities. In contrast, no significant enrichment by Cr, Mn, and Co was recorded. The cluster analysis revealed that the metallic workshops and the vehicle scrap workshops are the hottest functional areas.